Regulating tobacco - Rabin, Robert L.; Sugarman, Stephen D. (Oxford University Press, 2001)
This collection includes essays by 11 leading public health experts, economists, physicians, political scientists, and lawyers, whose activities encompass Congressional testimonies, Surgeon General's reports on youth smoking, and clinical trials for drugs for smoking cessation. They analyze specific strategies that have been used to influence tobacco use, including taxation, regulation of advertising and promotion, regulation of indoor smoking, control of youth access to cigarettes and other tobacco products, litigation, and subsidies of smoking cessation, and set them against the scientific findings about tobacco and the changing cultural and political setting against which policy decisions are being made.; This book is intended for scholars, lawyers, policy-makers, anti-tobacco activists, those interested in the development of tobacco regulations.
Keywords: Tobacco industry -- Government policy -- United States.; Cigarette industry -- Government policy -- United States.; Tobacco use -- Health aspects -- United States.; Tobacco use -- Prevention -- Government policy -- United States.; Cigarette smoke -- Health aspects -- United States.; Advertising -- Cigarettes -- Government policy -- United States.; Youth -- Tobacco use -- Prevention -- Government policy -- United States.; Medical policy -- United States.; Tobacco industry -- Law and legislation -- United States.; Smoking -- Law and legislation -- United States.; Tabac -- Industrie -- Politique gouvernementale -- États-Unis.; Cigarettes -- Industrie -- Politique gouvernementale -- États-Unis.; Cigarettes -- Publicité -- Politique gouvernementale -- États-Unis.; Politique sanitaire -- États-Unis.; SELF-HELP -- Substance Abuse & Addictions -- General.; PSYCHOLOGY -- Psychopathology -- Addiction.; Advertising -- Cigarettes -- Government policy; Cigarette industry -- Government policy; Cigarette smoke -- Health aspects; Medical policy; Smoking -- Law and legislation; Tobacco industry -- Government policy; Tobacco industry -- Law and legislation; Tobacco use -- Health aspects; United States